Monte Carlo verification of polymer gel dosimetry applied to radionuclide therapy: a phantom study. - Gear, J; Charles-Edwards, E; Partridge, M; Flux, G (2011)
This study evaluates the dosimetric performance of the polymer gel dosimeter 'Methacrylic and Ascorbic acid in Gelatin, initiated by Copper' and its suitability for quality assurance and analysis of I-131-targeted radionuclide therapy dosimetry. Four batches of gel were manufactured in-house and sets of calibration vials and phantoms were created containing different concentrations of I-131-doped gel. Multiple dose measurements were made up to 700 h post preparation and compared to equivalent Monte Carlo simulations. In addition to uniformly filled phantoms the cross-dose distribution from a hot insert to a surrounding phantom was measured. In this example comparisons were made with both Monte Carlo and a clinical scintigraphic dosimetry method. Dose-response curves generated from the calibration data followed a sigmoid function. The gels appeared to be stable over many weeks of internal irradiation with a delay in gel response observed at 29 h post preparation. This was attributed to chemical inhibitors and slow reaction rates of long-chain radical species. For this reason, phantom measurements were only made after 190 h of irradiation. For uniformly filled phantoms of I-131 the accuracy of dose measurements agreed to within 10% when compared to Monte Carlo simulations. A radial cross-dose distribution measured using the gel dosimeter compared well to that calculated with Monte Carlo. Small inhomogeneities were observed in the dosimeter attributed to non-uniform mixing of monomer during preparation. However, they were not detrimental to this study where the quantitative accuracy and spatial resolution of polymer gel dosimetry were far superior to that calculated using scintigraphy. The difference between Monte Carlo and gel measurements was of the order of a few cGy, whilst with the scintigraphic method differences of up to 8 Gy were observed. A manipulation technique is also presented which allows 3D scintigraphic dosimetry measurements to be compared to polymer gel dosimetry measurements without generating misleading errors due to the limited spatial resolution.